A model for fisheries patrol dispatch in the Canadian Atlantic offshore fishery - Millar, Harvey H.; Russell, Suzana N. (Ocean & coastal management, 2012)
Fisheries patrol routing involves routing a patrol vessel over a network of fishing grounds to maximize the deterrent effect of the patrol subject to trip length or budget constraints. This paper develops a prescriptive model for routing a multi-unit surveillance fleet through a set of fish stocks in the Canadian Atlantic offshore groundfish fishery. The decision problem is formulated as a 0–1 integer-programming model which is related to the well-known selective traveling salesman problem. In the fisheries patrol problem, the fishing grounds represent the cities, and all or a subset of grounds is visited on a given trip. We offer an efficient formulation and solution approach to the problem. Computational results for a hypothetical but realistic problem setting are provided. ► The Atlantic groundfish fishery is in need of protection due to the recent collapse of the industry from overfishing. ► The Department of Fisheries and Oceans is responsible for dispatching surface and aerial surveillance to protect the fishery. ► We provide dispatchers with a useful tool for planning surveillance tours for patrol vessels. ► We model the surveillance patrol dispatching problem using mathematical programming. ► We solve the mathematical model optimally using off-the-shelf software called CPLEX.